Development of interactive digital teaching materials based on 21st century skills in special purpose arabic language courses at STAI Attanwir Bojonegoro - Rahmawati, Nur Laila (At- Ta'lim : Jurnal Pendidikan, 2024)
Special Purpose Arabic Language refers to the teaching or learning of Arabic language tailored to specific needs or objectives. This means that Arabic language lessons are designed with a focus on its usage context in specific fields or activities, as opposed to a general approach to teaching Arabic. Special Purpose Arabic Language courses at the university level are tailored to specific needs and objectives in a professional context, producing graduates ready to face global challenges. The objectives of this research are (1) to analyze the process of developing interactive digital teaching materials based on 21st-century skills in Special Purpose Arabic Language courses at STAI Attanwir Bojonegoro, (2) to analyze the feasibility of interactive digital teaching materials based on 21st-century skills in Special Purpose Arabic Language courses at STAI Attanwir Bojonegoro, and (3) to analyze the effectiveness of interactive digital teaching materials based on 21st-century skills in Special Purpose Arabic Language courses at STAI Attanwir Bojonegoro. This research uses the Research and Development (R&D) method using the ADDIE model. Data collection techniques in this study use expert validation questionnaires, expert validation materials, student responses, and tests. The results of this research and development are as follows: (1) The development process consists of five steps: analysis, development, design, implementation, and evaluation, resulting in the production of interactive digital teaching materials based on 21st-century skills. (2) Based on validation results by experts, an average score of 90% was obtained. According to the Likert scale, the value of 90% falls into the category of very feasible because it is within the range of >61%. Meanwhile, the average percentage of student responses obtained an overall score of 88.5%, falling into the category of very feasible. (3) The results of the effectiveness test of teaching materials using a paired sample T-test showed a significant difference between pre-test and post-test scores with a significant value (2-tailed) of p = 0.000, <0.05. The null hypothesis (H0) in this study was rejected, and the alternative hypothesis (Ha) was accepted, indicating a significant difference between the two tests. Based on the data above, the developed teaching materials are effective in Special Purpose Arabic Language courses.